VAMPIR POLITIK INDONESIA SAMPUL DESAIN GRAFIS TABLOID DEMOKRAT EDISI 49 TANGGAL 23-30 JANUARI 2000 Representasi Senimannya Pada Masa Reformasi - -, Handriyotopo (Capture : Jurnal Seni Media Rekam, 2009)
The Press Independency that have been opening and tend to be bold to voice feeling and all condition starts to counter each other in their news, headlines, and illustrations. Including, PDIP ( Partai Demokratik Indoesia Perjuangan) shows in its tabloid ‘Demokrat’ that appears the slogan ‘yang penting srudukannya bung’ more over in which the cover illustrates Amien Rais as if a vampire creature ( makluk vampir). This illustration images encourage the PAN’ s (Partai Amanat Nasional anger. This seems to be a part of the graphics design function as a provocation to the consumers. Keyword : graphic design function